Engineering the mechanical characteristics of regenerated silk fibroin materials: the impact of chemical and physical modification strategies - Guan, Haitao; Ding, Fang; Xue, Ye; Zhao, Jinli (Frontiers in Chemistry, 2025)
In this study, an in-depth exploration was conducted on the mechanical properties of regenerated silk fibroin (RSF) materials through diverse processing modalities, encompassing wet pressing, humidity treatments at varying levels, and the incorporation of plasticizers. Notably, these approaches induced substantial modifications in the mechanical properties of RSF materials. The elastic strength of RSF exhibited a wide range, from 12.6 to 1,644.8 MPa; the ultimate strength spanned from 0.12 to 42.63 MPa, and the maximum elongation at break fluctuated between 0.67% and 614.38%. Additionally, the mechanisms underlying the effects of these distinct treatment methods were meticulously investigated. This fundamental research not only provides crucial insights into the modulation of silk fibroin’s mechanical properties but also holds significant promise for broadening its applications in the biomedical engineering domain, particularly in the pivotal fields of bone tissue and tendon regeneration.